Interventionist and interactionist dynamic assessment of argumentative writing in an EFL program - Kushki, Ali; Nassaji, Hossein; Rahimi, Mohammad (System (Linköping), 2022)
Standardized measures of language ability have held the status quo in L2 scholarship for decades. Complementary assessment practices, however, are gaining ground against the psychometric backdrop. In keeping with the trend, dynamic assessment (DA) embeds intervention within assessment. In this exploratory case study research, we tracked development in the abilities of five English-as-a-foreign-language (EFL) learners to write argumentative essays following the implementation of two types of DA: interventionist and interactionist. Data were collected from four one-on-one sessions between a mediator and the learners. Learners in the interactionist group (n = 3) outperformed those in the interventionist group (n = 2), as they demonstrated better understanding and application of target argumentative elements. Findings are discussed in light of the distinct features of the two DA types.